Mental health, legal capacity, and human rights - Stein, Michael Ashley; Mahomed, Faraaz 1985-; Pātil, Wīkrām 1964-; Sunkel, Charlene ca. 20./21. Jh; Restivo, Juliana ca. 20./21. Jh (Cambridge University Press, 2021)
Since adoption of the Convention on the Rights of Persons with Disabilities and the interpretive General Comment 1, the topic of legal capacity in mental health settings has generated considerable debate in disciplines ranging from law and psychiatry to public health and public policy. With over 180 countries having ratified the Convention, the shifts required in law and clinical practice need to be informed by interdisciplinary and contextually relevant research as well as the views of stakeholders. With an equal emphasis on the Global North and Global South, this volume offers a comprehensive, interdisciplinary analysis of legal capacity in the realm of mental health. Integrating rigorous academic research with perspectives from people with psychosocial disabilities and their caregivers, the authors provide a holistic overview of pertinent issues and suggest avenues for reform
Title from publisher's bibliographic system (viewed on 23 Aug 2021)
Introduction : a 'paradigm shift' in mental health care / Faraaz Mahomed, Michael Ashley Stein, Vikram Patel and Charlene Sunkel -- The alchemy of agency : reflections on supported decision-making, the right to health and health systems as democratic institutions / Alicia Ely Yamin -- Redefining international mental health care in the wake of the COVID-19 pandemic / Benjamin A. Barsky, Julie Hannah and Dainius Pūras -- Reparation for psychiatric violence : a call to justice / Tina Minkowitz -- Divergent human rights approaches to capacity and consent / Gerald L. Neuman -- From fairy tale to reality : a practical legal approach towards the global abolition of psychiatric coercion / Laura Davidson -- The "fusion law" proposals and the CRPD / John Dawson and George Szmukler --
- Contextualising legal capacity and supported decision making in the Global South : experiences of homeless women with mental health issues from Chennai, India / Mrinalini Ravi, Barbara Regeer, Archana Padmakar, Vandana Gopikumar and Joske Bunders -- The potential of the legal capacity law reform in Peru to transform mental health provision / Alberto Vásquez Encalada -- Advancing disability equality through supported decision making : the CRPD and the Canadian constitution / Faisal Bhabha -- Decisional autonomy and India's Mental Healthcare Act, 2017 : a comment on emerging jurisprudence / Soumitra Pathare and Arjun Kapoor -- Towards resolving damaging uncertainties : progress in the United Kingdom and elsewhere / Adrian D. Ward -- "The revolution will not be televised" : recent developments in mental health law reform in Zambia and Ghana / Heléne Combrinck and Enoch Chilemba --
- Supported decision-making and legal capacity in Kenya / Elizabeth Kamundia and Ilze Grobbelaar-du Plessis -- Seher's "circle of care" model in advancing supported decision making in India / Bhargavi V. Davar, Kavita Pillai and Kimberly LaCroix -- The Swedish personal ombudsman : support in decision-making and accessing human rights / Ulrika Järkestig Berggren -- Strategies to achieve a rights based approach through WHO quality rights / Michelle Funk, Natalie Drew Bold, Joana Ansong, Daniel Chisholm, Melita Murko, Joyce Nato, Sally-Ann Ohene, Jasmine Vergara and Edwina Zoghbi -- The clubhouse model : a framework for naturally occurring supported decision making / Joel D. Corcoran, Cindy Hamersma and Steven Manning -- Mind the gap : researching "alternatives to coercion" in mental health care / Piers Gooding --
- Psychiatric advance directives and supported decision-making : preliminary developments and pilot studies in California / Christopher Schnieders, Elyn R. Saks, Jonathan Martinis and Peter Blanck -- Community-based mental health care delivery with partners in health : a framework for putting the CRPD into practice / Stephanie L. Smith -- Lived experience perspectives from Australia, Canada, Kenya, Cameroon and South Africa - conceptualizing the realities / Charlene Sunkel, Andrew Turtle, Sylvio A Gravel, regi Mwenja and Marie Angele Abanga -- In the pursuit of justice : advocacy by and for hyper-marginalized people with psychosocial disabilities through the law and beyond / Lydia X. Z. Brown and Shain M. Neumeier -- The Danish experience of transforming decision-making models / Dorrit Cato Christensen -- The use of patient advocates in supporting people with psychosocial disabilities / Aikaterini Nomidou --
Keywords: Convention on the Rights of Persons with Disabilities and Optional Protocol / (2007 March 30); Mental health laws; Mental health policy